OPTIMIZING ENGLISH LANGUAGE LEARNING THROUGH INNOVATIVE METHODS AND SUPPORTING ACTIVITIES AT MA NURUL HIKAM - Hasanah, Jami’atul; Pramudita, Selvi; Romadoni, Sauqi (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
This community service program was carried out at MA Nurul Hikam Situbondo with the aim of enhancing the quality of English language learning through the application of innovative, interactive methods and supporting non-formal activities. The initiative addressed key challenges such as monotonous teaching methods, lack of visual learning media, and the absence of extracurricular platforms for language practice. The strategies implemented included the use of communicative and participatory classroom techniques, the development of educational posters as visual aids, and the revitalization of an English Club to support students’ speaking confidence. Based on Participatory Action Research (PAR) and descriptive qualitative methods, the program showed positive outcomes, including increased student engagement, creativity, and confidence in using English both in and outside the classroom. The results highlight the importance of integrating formal instruction with creative and non-formal learning activities to foster holistic language development, especially in rural madrasah settings with limited resources.